Mechanical behavior of architectured photosensitive silicone membranes: Experimental data and numerical analysis. Issue 6 (26th April 2017) - Machado, G.; Stricher, A.; Chagnon, G.; Favier, D.
ABSTRACT: The aim of this article is to provide an experimental and modeling study of an architectured photosensitive silicone membrane. Mechanical properties are dependent of UV doses used to alter the local cross-link density, resulting in a direct effect on the macroscopic mechanical behavior. A series of mechanical tests were carried out to characterize the mechanical behavior of each phase. Results are presented for various types of loading, including uniaxial, planar, and equibiaxial loading cases, for the UV irradiated and the nonirradiated material. Using the bulge test with an architectured sample, the global stretchability with minimum boundary condition perturbations was investigated. To further explore the unusual properties offered by silicone graded membranes, finite element analysis of graded architecture was performed to try to predict the stress-strain response in the bulge test. Soft-to-hard transition is tested and the macroscopic influence of interface was observed.